2004
DOI: 10.1111/j.1523-1755.2004.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in renal disease: Relationship to phenotype and genetic variation in the gene encoding adiponectin

Abstract: The present cross-sectional study demonstrates that, whereas genetic variations seem to have a minor impact on circulating adiponectin levels, lower visceral fat mass and type 1 diabetes mellitus are associated with elevated plasma adiponectin levels in ESRD patients. Furthermore, low levels of adiponectin are associated with inflammation in ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
111
5
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 35 publications
18
111
5
4
Order By: Relevance
“…These findings indicate that adiponectin might have beneficial effects against renal dysfunction including MC disorders. In some studies, it was reported that plasma adiponectin levels were elevated in patients with CKD (Stenvinkel et al 2004, Guebre-Egziabher et al 2005. It is suggested that the elevated plasma adiponectin levels can work as a compensatory mechanism to attenuate the progression of glomerular dysfunction in the patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that adiponectin might have beneficial effects against renal dysfunction including MC disorders. In some studies, it was reported that plasma adiponectin levels were elevated in patients with CKD (Stenvinkel et al 2004, Guebre-Egziabher et al 2005. It is suggested that the elevated plasma adiponectin levels can work as a compensatory mechanism to attenuate the progression of glomerular dysfunction in the patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that plasma adiponectin levels are elevated when renal function is impaired -as early as CKD stage III -and particularly in proteinuric patients (Guebre-Egziabher et al 2005). Another study demonstrated that plasma adiponectin levels were markedly elevated in patients with end-stage renal disease (Stenvinkel et al 2004). It has been considered that the rise in plasma adiponectin that occurs during renal function deterioration represents an adaptive response to the altered metabolic profile associated with a high cardiovascular risk in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…These include a benefit from the better nutritional status typically seen in obese individuals, and which provides better protein and energy reserves in the face of acute illness, and a higher muscle mass with enhanced antioxidant capacity 63 and lower circulating actin and higher plasma gelsolin levels, 71 which are associated with better outcomes. Other hypothetically beneficial characteristics of obesity include a more stable hemodynamic status with mitigation of stress responses and heightened sympathetic and renin-angiotensin activity; 72 increased production of adiponectines 73 and soluble tumor necrosis factor alfa receptors 74 by adipose tissue neutralizing the adverse effects of tumor necrosis factor alfa; enhanced binding of circulating endotoxins 75 by the characteristically higher cholesterol levels seen in obesity; and sequestration of uremic toxins by adipose tissue.…”
Section: Obesity In Patients With Advanced Kidney Disease: the Need Fmentioning
confidence: 99%
“…[7] There was also a significant negative relationship between adiponectin and two biomarkers of inflammation, hsCRP and fibrinogen. Thus, it has been suggested that hypoadiponectinemia may also serve as a marker of increased inflammatory status in end stage renal disease (ESRD) patients in the study by Stenvinkel et al [23] Moreover, it has been established that adiponectin can accumulate in the vascular wall when the endothelial barrier is damaged. This accumulation may also contribute to hypoadiponectinemia in patients with proteinuria.…”
Section: Tablementioning
confidence: 99%